Laccase-mediated formation of mesoporous silica nanoparticle based redox stimuli-responsive hybrid nanogels as a multifunctional nanotheranostic agent. Issue 39 (22nd September 2016) - Qiao, Li; Wang, Xia; Gao, Yawei; Wei, Qingcong; Hu, Wen; Wu, Lei; Li, Pei; Zhu, Rongrong; Wang, Qigang
Abstract : A laccase-mediated formation of mesoporous silica nanoparticle-based redox stimuli-responsive hybrid nanogels has been developed for drug delivery and ultrasound imaging. Abstract : In this work, we designed a new hybrid nanogel with redox responsive polymer gel shells and mesoporous silica nanoparticles (MSNs) cores via laccase-mediated radical polymerization. The successful coating of the responsive gel shells on the MSNs was confirmed by the morphology and increased diameters of the particles as determined by transmission electron microscopy (TEM) and dynamic light scattering (DLS). As observed by scanning transmission electron microscopy (STEM) and energy dispersive X-ray spectroscopy (EDS), the presence of the element S around the MSNs further confirmed the formation of the gel shell. When loaded with doxorubicin (DOX), these hybrid nanogels had a significantly higher cumulative DOX release in a reductive environment than that found under physiological conditions. The MSNs with mesoporous channels were loaded with perfluorohexane (PFH) for ultrasound imaging, which was enhanced by the presence of the elastic gel shells.